BREXIT REFERENDUM AND MEDIA COVERAGE: AN APPRAISAL (Journal of European Studies (JES), 2018)
On June 23, 2016 the British people voted to leave the EU in a nation-wide referendum. Politically the vote brought with it greater uncertainty and instability not only domestically but regionally. This warranted a broader examination of events that led the UK towards this decision. Popular narrative holds immigration, economy, and a highly bureaucratic European Union as the core reasons.This study analyzes the significance and influence that media coverage exerted during the Brexit vote. This paper undertakes content analysis of influential newspapers at local, regional, and international level under the theoretical domain of ‘agenda setting’, ‘propaganda’ and ‘manufacturing consent’. It appraises the role played by regional and local press in managing and creating perception amongst general public vis-à-vis UK membership in the European Union. According to several surveys and statistics, media propagated misinformation and populist narratives that eventually tilted the result in favor of exit.
Keywords: Brixit,; Media role,; Agenda setting